Simultaneous Determination of Uric Acid and Caffeine by Flow Injection Using Multiple-Pulse Amperometry - Wong, Ademar [UNESP] (2023)
The present study reports the development and application of a flow injection analysis (FIA) system for the simultaneous determination of uric acid (UA) and caffeine (CAF) using cathodically pretreated boron-doped diamond electrode (CPT-BDD) and multiple-pulse amperometry (MPA). The electrochemical profiles of UA and CAF were analyzed via cyclic voltammetry in the potential range of 0.20–1.7 V using 0.10 mol L−1 H2SO4 solution as supporting electrolyte. Under optimized conditions, two oxidation peaks at potentials of 0.80 V (UA) and 1.4 V (CAF) were observed; the application of these potentials using multiple-pulse amperometry yielded concentration linear ranges of 5.0 × 10−8–2.2 × 10−5 mol L−1 (UA) and 5.0 × 10−8–1.9 × 10−5 mol L−1 (CAF) and limits of detection of 1.1 × 10−8 and 1.3 × 10−8 mol L−1 for UA and CAF, respectively. The proposed method exhibited good repeatability and stability, and no interference was detected in the electrochemical signals of UA and CAF in the presence of glucose, NaCl, KH2PO4, CaCl2, urea, Pb, Ni, and Cd. The application of the FIA-MPA method for the analysis of environmental samples resulted in recovery rates ranging between 98 and 104%. The results obtained showed that the BDD sensor exhibited a good analytical performance when applied for CAF and UA determination, especially when compared to other sensors reported in the literature.